New Entrepreneurship Creation Model In The Community Of Kebonagung Village, Ploso District, Jombang Regency As A Form Of Puskad Business Incubator Collaboration - Chusnul Rofiah; Sapto Roedy Widijanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This community service activity shows that the Puskad business incubator as part of the community can remain closely connected with the community that gave birth to it. For example, the problem of poverty which continues to haunt social life must continue to be eradicated. This can be alleviated, for example, by entrepreneurship or business development. Meanwhile, business development continued to develop over time, resulting in the rise of social media. With this service, we can see that people must share knowledge and experience with each other so that we can develop together. Therefore, answers from academics to problems and society can be displayed here. Using the participatory action research method, it was found that the way to increase the younger generation's understanding and knowledge of social media is to start with interaction. The differences that arise from social media training can be seen through the accuracy of conveying information to the appropriate target audience, equipment and communication facilities between creative actors, and budget conditions to meet the training and creativity needs of the community. The results of content creator training for entrepreneurs are: 1) Improved Communication Skills; 2) Increased Brand Awareness; 3) Increase interaction with customers; 4) Increase Conversions and Sales; 5) Marketing Cost Savings